2015
DOI: 10.1111/ajps.12155
|View full text |Cite
|
Sign up to set email alerts
|

The Temporary Importance of Role Models for Women's Political Representation

Abstract: I n the last several decades, the political representation of women has improved sharply, thanks in part to the introduction of legislative quotas in many countries. At the same time, worldwide, only one in five members of parliament are female, on average, and even Nordic countries, with about 42% women in parliament, have yet to reach full gender equality in this area. There are many reasons for the underrepresentation of women in politics. Following an influential model of political recruitment (Norris 1997… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(85 citation statements)
references
References 75 publications
(85 reference statements)
5
73
1
6
Order By: Relevance
“…Banerjee et al (2017) use a similar approach to show that seat reservation had effects on incumbency and challenger entry. In the current work, I complement this literature by investigating the effects of female politicians across levels of government rather 2 Studies of the legacy effects of female politicians on future candidacies in local politics include Nagarajan et al (2011) for India and Gilardi (2014) for Switzerland. than within the same body.…”
Section: Policy Background and Related Literaturementioning
confidence: 99%
“…Banerjee et al (2017) use a similar approach to show that seat reservation had effects on incumbency and challenger entry. In the current work, I complement this literature by investigating the effects of female politicians across levels of government rather 2 Studies of the legacy effects of female politicians on future candidacies in local politics include Nagarajan et al (2011) for India and Gilardi (2014) for Switzerland. than within the same body.…”
Section: Policy Background and Related Literaturementioning
confidence: 99%
“…In districts which had quota‐appointed female leaders, girls had higher aspirations and better educational outcomes compared to districts with no quote law in place (and the leader was male). Similarly, Gilardi () found that the presence of a female candidate in Swiss municipal elections encouraged other women to run for office. However, this is particularly the case the first time a woman runs for office in a given area, suggesting that role models might be of particular relevance when they serve as trailblazers who demonstrate that a goal is indeed attainable for members of one's group.…”
Section: The Effects Of Quotas and Affirmative Actionmentioning
confidence: 97%
“…Asimismo, Tras el estudio de elecciones locales en Estados Unidos, Bhalotra, Clots-Figueras y Iyer (2013) reportaron resultados similares, incluso cuando no existen cuotas de género. Por su parte, Gilardi (2015) señala que también hay efectos positivos en la elección de mujeres en municipios colindantes o cercanos a aquellos donde, en elecciones anteriores, hubiese triunfado una mujer. Para el caso de Chile, Martínez Ossa y Navia (2017) también reportan más presencia de candidatas en lugares donde antes hubo alcaldesas, incluso cuando se excluye a aquellas mujeres que buscaban la reelección.…”
Section: El Efecto Contagiounclassified